Cataract surgery the state of the art - Fine, I. Howard; Packer, Mark; Hoffman, Richard S. (Thorofare : SLACK Incorporated, 2002)
Cataract Surgery CR-ROM: The State of the Art provides a comprehensive view of this ever-evolving procedure as performed by expert surgeons, led by world renowed surgeon, Dr. I. Howard Fine.
System requirements: Pentium-based PC or above, Microsoft Windows 95, 98, or later, 6X CD-ROM, 16MB of RAM (32 MB preferred), 10MB or hard disk storage, 1 MB (or higher) SGVA video card, 8-bit Sound Blaster-compatible sound card, QuickTime 5.0 or higher for Windows (included), For macintosh: power PC or above, 16 MB of RAM (32 MB preferred), 10 MB of hard disk storage, MAc OS version 8.6 or later.
Keywords: Cataract -- surgery; Cataract Extraction